Contributions to the taxonomy of Neotropical Cyparium Erichson (Coleoptera: Staphylinidae: Scaphidiinae), with the description of five new species - von Groll, Elisa; Lopes-Andrade, Cristiano (European Journal of Taxonomy, 2022)
The genus Cyparium Erichson, 1845 (Staphylinidae, Scaphidiinae, Cypariini) comprises 55 species, distributed mainly in the Neotropical and Oriental regions. Twenty-four species are known from the Neotropical region, but only eight species are reported from Brazil. In this paper we describe five new species and redescribe two species of Brazilian Cyparium, as follows: Cyparium achardi sp. nov., C. lescheni sp. nov., C. loebli sp. nov., C. newtoni sp. nov., C. pici sp. nov.; Cyparium collare Pic, 1920; and Cyparium oberthueri Pic, 1956. We provide images of adult males and females and their dissected parts, and information on host fungi whenever available. We also provide a comparative plate of dorsal colour patterns of Neotropical Cyparium.